2017
DOI: 10.17722/ijme.v8i3.292
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality, Abnormal Audit Fee and Auditor Attributes

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…The result aligns with the postulation that larger audit firms decrease earnings management. The result is in tandem with studies (Ogujiofor et al, 2017;Oladipupo & Monye-Emina, 2016).…”
Section: Results and Discussion Of Findingssupporting
confidence: 87%
See 1 more Smart Citation
“…The result aligns with the postulation that larger audit firms decrease earnings management. The result is in tandem with studies (Ogujiofor et al, 2017;Oladipupo & Monye-Emina, 2016).…”
Section: Results and Discussion Of Findingssupporting
confidence: 87%
“…The listed firms are expected to perform a mandatory statutory audit to increase investors' confidence in the financial statements. Several studies (e.g., (Ogujiofor, Anichebe, & Ozuomba, 2017;Oladipupo & Monye-Emina, 2016)) have shown that audit type improves earnings quality and are of the view that large audit firms promote high financial reporting quality and invariably high earning quality. Conversely, studies by Choi, Kim, and Zang (2010); Kinney Jr and Libby (2002) and Libby, Rennekamp, and Seybert (2015) claim that economic bonding and client bargaining may compromise auditors' independence.…”
Section: Model Specification and Measurement Of Variablesmentioning
confidence: 99%
“…(Dao et. al., 2012;Muzatko and Teclezion, 2016;Nkemjika et al, 2017;Martinez and Moraes 2017;Ganesan et al, 2019;Alves 2021) provided evidence of a positive relationship between audit fees and financial reporting quality. Muzatko and Teclezion (2016) investigated the relationship between audit fees and earnings management as a proxy for financial reporting quality, their results…”
Section: Hypotheses Developmentmentioning
confidence: 99%